Pengaruh Ekonomi Makro, Harga Minyak Dunia, dan Rasio Keuangan terhadap Harga Saham pada Perusahaan Konstruksi di Indonesia - Eka Setya Adrianto (Journal of Trends Economics and Accounting Research, 2024)
This research investigates the influence of macroeconomic and internal company factors on the share prices of construction companies in Indonesia. Through analysis of 111 observations of public companies from 2012 to 2021, this research finds that GDP growth has a significant positive influence on stock prices, with every 1% increase in GDP increasing stock prices by 10.76%. This shows that improving economic conditions increases construction companies' performance expectations. Inflation positively affects stock prices, with every 1% increase increasing stock prices by 9.87%. On the other hand, increases in interest rates and exchange rates have a negative impact, with every 1% increase reducing stock prices by 0.76% and 3.67%, respectively. The study also revealed that rising oil prices reduce stock prices by 0.77% for every 1% increase, indicating the negative impact of oil price fluctuations. Internal company factors such as ROE and DER are also influenced, where every 1% increase in ROE increases share prices by 2.08%, while a 1% increase in DER reduces share prices by 0.33%. These findings provide important insights into how macroeconomic and internal company financial factors influence share prices in the Indonesian construction sector, guiding investors and companies in making strategic decisions, especially in the construction sector.